Strategi Pengembangan SDM di Dinas Pariwisata Pemuda dan Olahraga Melalui Program Desa Wisata Cibeusi Kabupaten Subang - Sumiati Sumiati; Cucu Sugiarti; Rachmat Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze the strategy of the Subang District Youth and Sports Tourism Office in the development (Capacity Building) through the village tourism program in Subang Regency. This research is motivated by the influence of the quality of human resources in the development of tourism in an area. So that the strategy that must be used must be in accordance with the objectives of tourism development in order to be competitive and efficient for the local community. The research method used is a qualitative description that is to provide an objectively appropriate description or explanation related to the state of the announcement by interview and observation and based on literature studies from documents, laws, and from the internet based on the problem under study. The focus of this research is based on the dimensions of HR development strategies (Capacity Building), including: HR development strategies, organizational strengthening strategies, and institutional reform strategies. The results of this study indicate that the role of the Subang Regency's Youth and Sports Tourism Office is considered to be lacking because of the limited human resources that are owned by both the community and human resources department.